2012
DOI: 10.1002/chem.201102678
|View full text |Cite
|
Sign up to set email alerts
|

Transmetallation Versus β‐Hydride Elimination: The Role of 1,4‐Benzoquinone in Chelation‐Controlled Arylation Reactions with Arylboronic Acids

Abstract: The formation of an atypical, saturated, diarylated, Heck/Suzuki, domino product produced under oxidative Heck reaction conditions, employing arylboronic acids and a chelating vinyl ether, has been investigated by DFT calculations. The calculations highlight the crucial role of 1,4-benzoquinone (BQ) in the reaction. In addition to its role as an oxidant of palladium, which is necessary to complete the catalytic cycle, this electron-deficient alkene opens up a low-energy reaction pathway from the post-insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 96 publications
2
36
0
Order By: Relevance
“…Their results indicate that benzoquinone prevents the occurrence of β-hydride elimination after the initial migratory insertion of olefin into the Pd−Ar bond, and instead, another aryl group is transmetalated to the Pd center. 181 In the same study, a comparison between M06 and B3LYP-D3 methods showed the former to lower the relative energies of the species involved while still predicting the same reactivity trend.…”
Section: Suzuki−miyauramentioning
confidence: 91%
“…Their results indicate that benzoquinone prevents the occurrence of β-hydride elimination after the initial migratory insertion of olefin into the Pd−Ar bond, and instead, another aryl group is transmetalated to the Pd center. 181 In the same study, a comparison between M06 and B3LYP-D3 methods showed the former to lower the relative energies of the species involved while still predicting the same reactivity trend.…”
Section: Suzuki−miyauramentioning
confidence: 91%
“…[5] The mechanistic implications of the base have been analyzed by means of experimental [3,6,7] and theoretical methods. [4,[8][9][10][11] Two possible pathways for the transmetalation step have been proposed depending on the point of entry of the hydroxide anion in the reaction mechanism (Scheme 1). [7] The first route, the boronate mechanism, path A, suggests the activation of the boronic acid by nucleophilic attack of the base to form the corresponding boronate species, which replaces the halide ligand in the coordination sphere of the Pd catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…For the domino Heck/Suzuki reaction, we proposed a mechanism involving a chelation-controlled carbopalladation step,11 which was supported by recent density functional theory (DFT) calculations, highlighting the crucial role of p -BQ in the catalytic process 12. Since the diarylation reaction requires an olefin equipped with a metal coordinating group, control of the stereochemical outcome of the reaction should be possible by choosing an appropriate chiral catalyst-directing moiety, allowing the generation of diastereomerically enriched σ-intermediate II (Scheme 1).…”
Section: Introductionmentioning
confidence: 62%
“…In the same manner, different batches of solvent used in the screening processes presumably contained varying water concentrations, which could have affected the reaction outcome. Previous work by our group has also illustrated the importance of water in an achiral version of the chelation-controlled Heck/Suzuki domino reaction 12. We therefore decided to investigate the effect of water content on the outcome of this reaction.…”
Section: Resultsmentioning
confidence: 99%